There and Back Again - Owen Hopkins (Footprint)
This essay explores the defining role that council housing has played in populist politics in Britain from the post-war era to the present. Central to this was Margaret Thatcher’s Right to Buy scheme – an archetypal populist policy that became totemic of her broader reconfiguration of British society. Building on the demonisation of council housing that paved the way for Right to Buy, today, it stands as the implicit foil for the present right-wing government’s populist advocation of ‘beauty’ (i.e. traditional styles) as a way of removing objections to future development. Meanwhile, the populist left argues for a return to the mass council house building of the post-war era, despite the recent success of small-scale, tactical council housing projects, such as those by Peter Barber Architects. The essay argues that the polarised and asymmetrical nature of this debate, conflating questions of aesthetics, typology and planning and tenure type, is typical of populist politics, ensuring a middle ground is by definition impossible. The essay concludes with the contention that if populist politics tends towards a monocultural architecture and urbanism, then a built environment that allows room for different forms, ideas and agendas may itself help foster a politics of pluralism.